Pro XAML with C# Application Development Strategies (covers WPF, Windows 8.1, and Windows Phone 8.1) - James, Buddy. (Apress : Imprint: Apress, 2015)
Pro XAML with C#: Application Development Strategies is your guide to real-world development practices on Microsoft’s XAML-based platforms, with examples in  WPF, Windows 8.1, and Windows Phone 8.1. Learn how to properly plan and architect an application on one or more of these platforms for a robust, scalable solution. In Part I, authors Buddy James and Lori Lalonde introduce you to XAML and reveal proven techniques for developing successful line-of-business applications. You’ll also find out about some of the conflicting needs and interests that you might encounter as an enterprise XAML developer. Part II begins to lay the groundwork to help you properly architect your application, providing you with a deeper understanding of domain-driven design and the Model-View-ViewModel design pattern. You will also learn about proper exception handling and logging techniques, and how to cover your code with unit tests to reduce bugs and validate your design. Part III explores implementation and deployment details for each of Microsoft’s XAML UIs, along with advice on deploying and maintaining your application across different devices using version control repositori es and continuous integration. Pro XAML with C#: Application Development Strategies is for intermediate to experienced developers looking to improve their professional practice. Readers should have experience working with C# and at least one XAML-based technology (WPF, Silverlight, Windows Store, or Windows Phone). .